Long time asymptotics for homoenergetic solutions of the Boltzmann equation. Hyperbolic-dominated case. (9th June 2020) - James, Richard D; Nota, Alessia; Velázquez, Juan J L
Abstract: In this paper we continue the formal analysis of the long-time asymptotics of the homoenergetic solutions for the Boltzmann equation that we began by James et al (2019 J. Nonlinear Sci. 29 1943–73). They have the form f x, v, t = g v − L t x, t where L t = A I + t A − 1 where A is a constant matrix. Homoenergetic solutions satisfy an integro-differential equation which contains, in addition to the classical Boltzmann collision operator, a linear hyperbolic term. Depending on the properties of the collision kernel the collision and the hyperbolic terms might be of the same order of magnitude as t → ∞, or the collision term could be the dominant one for large times, or the hyperbolic term could be the largest. The first case has been rigorously studied by James et al (2019 Arch. Ration. Mech. Anal. 231 787–843). Formal asymptotic expansions in the second case have been obtained by James et al (2019 J. Nonlinear Sci. 29 1943–73). All the solutions obtained in this case can be approximated by Maxwellian distributions with changing temperature. In this paper we focus in the case where the hyperbolic terms are much larger than the collision term for large times (hyperbolic-dominated behaviour). In the hyperbolic-dominated case it does not seem to be possible to describe in a simple way all the long time asymptotics of the solutions, but we discuss several physical situations and formulate precise conjectures. We give explicit formulae for the relationship between density, temperature and entropy for these solutions. These formulae differ greatly from the ones at equilibrium.